Preservice teachers’ experiences with classroom management in the virtual class: a case study approach - Hojeij, Zeina; Baroudi, Sandra; Meda, Lawrence (Frontiers in Education, 2023)
The present study explores the experiences of Emirati female preservice teachers who are completing their internship teaching practice virtually due to the COVID-19 pandemic. This qualitative study focuses on virtual classroom management. Participants were preservice teachers (n = 18) completing their undergraduate degrees in Early Childhood Education at a federal university in the United Arab Emirates (UAE). Data collected from interviews resulted in four themes related to classroom management: challenges, opportunities, performance factors, and suggestions for improvement. The findings revealed that the preservice teachers considered virtual learning an opportunity. However, the main challenge was that the preservice teachers had no prior training in online classroom management and had to create their own strategies. Training on the technology used for virtual learning is important for both teachers and students to achieve satisfactory learning experiences.